(untitled) (Research, Society and Development, 2025)
Osteolipomas consist of a metaplastic variation of lipoma, which are considered very rare when presented in an intraosseous location in the head and neck region. They usually present as a painless, slow-growing mass that, when properly diagnosed and treated, have a satisfactory prognosis and low recurrence rates. This paper aims to report the case of a 49-year-old female patient, who attended the clinic complaining of a painless lesion in the maxilla, discovered through a panoramic radiograph performed for orthodontic documentation purposes. Imaging exams showed a well-defined irregular mass, moderately calcified with a heterogeneous appearance, projecting from the inner cortex of the anterior wall of the left maxilla into the ipsilateral maxillary sinus, with its central portion hypodense and surrounded by tissue of greater hyperdensity. After performing an incisional biopsy and obtaining a pathological result of osteolipoma, resection of the lesion was scheduled in a hospital setting using the Le Fort I osteotomy technique. The material was again sent for histopathological analysis, confirming the previous diagnosis. Under 12 months of postoperative follow-up, the patient showed no complaints or clinical and radiographic signs of lesion recurrence. The correct prior diagnosis is significant for choosing the best approach for the definitive treatment of lesions. The use of Le Fort I osteotomy not only allowed direct visualization of the involved area, facilitating complete removal of the lesion, but also avoided unnecessary destruction of the maxilla structure.